Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11655-011-0724-0
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, double-blinded and double-dummy trial of the effect of Tongjiang Granule (通降颗粒) on the nonerosive reflux disease of and Gan (肝)-Wei (胃) incoordination syndrome

Abstract: TJG showed a definite effect on the treatment of NERD with Gan-Wei incoordination syndrome, and it could improve the quality of life of NERD patient without obvious toxic and side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Currently, it has become a common model in the diagnosis and treatment of TCM clinical practice [26]. The mode of disease-syndrome combination has been successfully and widely applied to a variety of clinical diseases including restenosis after percutaneous coronary intervention [27], unstable angina [28], cancer [29], nonerosive reflux disease [30], rheumatoid arthritis [31], posthepatitis B liver cirrhosis [32], liver fibrosis [33], poststroke dysphagia [34], menopausal symptoms [35], and psoriasis vulgaris [36]. …”
Section: Disease-syndrome Combination Is a New Mode For Treatment mentioning
confidence: 99%
“…Currently, it has become a common model in the diagnosis and treatment of TCM clinical practice [26]. The mode of disease-syndrome combination has been successfully and widely applied to a variety of clinical diseases including restenosis after percutaneous coronary intervention [27], unstable angina [28], cancer [29], nonerosive reflux disease [30], rheumatoid arthritis [31], posthepatitis B liver cirrhosis [32], liver fibrosis [33], poststroke dysphagia [34], menopausal symptoms [35], and psoriasis vulgaris [36]. …”
Section: Disease-syndrome Combination Is a New Mode For Treatment mentioning
confidence: 99%
“…The randomized methods were described in detail in all studies [ 9 – 22 ], which were considered as randomized blocks [ 13 ], sealed envelopes [ 12 , 14 , 20 ], and random number tables [ 9 , 10 , 14 – 19 , 21 , 22 ]. Hence, we considered them low risk in the aspect of selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we considered them low risk in the aspect of selection bias. Almost none of the studies reported blinded methods, which were regarded as high risk in terms of performance bias except for the study reported by Li et al [ 13 ]. Detection bias was low risk in two studies [ 13 , 14 ], but it was unclear in other studies [ 9 – 12 , 15 – 22 ] in the absence of the blinding of outcomes assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations